Improving the Students’ Ability to Play Music Instruments Using Contemporary Genre Music Composition in SLB A Karya Murni Medan - Juliet Panggabean, Ance; Batubara, Junita; Saragih, Ronald Herico; Rosyo, Pandang (Komposisi: Jurnal Pendidikan Bahasa, Sastra, dan Seni, 2025)
This research aims to improve the ability to play musical instruments using contemporary genre as a music playing activity that has never been done at SLB A Karya Murni Medan.  This activity is based on the lack of ability to play musical instruments for each child and the lack of optimal music learning by using contemporary genre as their musical repertoire. Contemporary genre are very interesting because they use elements of tone color, emphasis on mixing instrument sounds, melody as a variation of pitch in rhythm (time), micropolyphonic harmony, new sounds and non-functional vertical harmony, free rhythmic patterns. and complex and rhythmic micropatterns. The research subjects of SLB A students were 13 students. This research uses qualitative methods with a descriptive analysis approach in describing phenomena that occur related to efforts to improve the ability to play musical instruments using contemporary genre or children with special needs at SLB A Karya Murni Medan. It is hoped that the results of the research can make music playing activities more interesting and provide benefits for blind children such as playing instruments, learning rhythmic patterns, singing melodies, making movements while singing collectively using contemporary musical compositions and holding small musical performances for SLB A students Murrni Medan's work.